Originally Posted by
gbux512 ok so moving down the line of problems, i have one more thats giving me trouble, y=x, y=0 x=2 x=4, about x=1
so i start off taking the integral from 2-4 of (1-y)^2 -(1-0)^2 dy
then i foil it out to get 1-2y+y^2 -1 dy
then i integrate it *after ditching the 1's) and get -y^2 + (y^3)/3 |2,4
sooo im now at -4^2 + (4^3)/3- (2^2+ (2^3)/3)
which simplifies out to 48/3 + 64/3 + -12/3 -8/3 =92(pi)/3
this is obviously not the answer in the back of the book, but after picking my brain for HOURS i cant find my flaw :/